Comparison of The Pass-Through Speed Models of Different Markets: An Empirical Study of the Markets of Mainland China and Taiwan - Ho, Chi Ming; Lin, Wu Yih (UUM Press, 2020)
This paper adopted the Boone Indicator, developed by Boone et al. (2008) and Van Leuvensteijn et al. (2011; 2013), to investigate the influence of different pass-through spread models in the competition among banks in emerging markets. With the market share of banks as a dependent variable and marginal cost as an independent variable, this paper probed into the competition among banks regarding the loan market to determine whether competition on the loan interest rates of banks affected the pass-through of monetary policy-related interest rates. After analyzing approximately 5,657 entries of records of the banking industries in Taiwan and mainland China, this paper reached three significant conclusions: 1) the Boone Indicator Model pointed out that, competition in the banking market of mainland China was more intense than that of Taiwan; 2) empirical research based on the Interest Rate Spread Model indicated that the spread of mainland China was lower than that of Taiwan; 3) the Passthrough Speed Model implied that, the interest rate sensitivity of the market of mainland China was higher than that of the Taiwan market. The above results indicate that the influence of monetary policy pass-through on the interest rate of the market in mainland China is faster than in Taiwan.